Factors Affecting Quality Nursing Care Delivery at Ridge Hospital: Perspectives of Nurses - Bour, M (University Of Ghana, 2014)
The factors affecting quality nursing care delivery from the perspective of nurses were explored at the Ridge Hospital. Ten nurses with two to fifteen years of working experiences were purposively sampled from the medical and surgical wards and interviewed using a semi structured interview guide after informed consent had been obtained from them. The interviews were audio tape recorded and transcribed verbatim. Additionally, data collected from participants were analysed using thematic content analysis approach adopting Donabedian's model of quality care as a framework. Quality nursing care was perceived by the nurses to mean care which is holistic, individualized and tailored to meet specific needs of patients. Findings of the study revealed that nurses in the hospital perform various activities; some of which include admission of patients, assessment of patients, educating patients on health matters, assisting patients with activities of daily living and communicating with colleagues and patients about patients' care. Nevertheless, it was observed that these nurses could not do much for patients because of several factors such as inadequate human resources, material resources and lack of motivational packages. It was therefore recommended that management should ensure that material and human resources are adequately available to facilitate quality nursing care delivery in the hospital. Also, clinical supervision in the hospital must be strengthened to ensure all round provision of quality nursing care.
Thesis (MSc)
Keywords: Nursing Care; Health Care Delivery; Ghana